Potential effect of social support on perceived stress and anxiety in college students during public health crisis: Multiple interactions of gender - Taibo He; Chia Ching Tu; Zhi Wang; Danna Hao; Xiaozhou Huang (PLoS ONE, 2025)
The COVID-19 pandemic has affected college students, leading to increased anxiety and emotional distress. This study investigated how perceived public health crises relate to anxiety levels in college students, and how social support and gender influence this relationship. Data from 3,165 college students from six universities in Shaanxi Province, China, were collected and analyzed by using AMOS and SPSS PROCESS 4.0. Results showed that perceived COVID-19 risk significantly impacted anxiety levels, and social support moderated this relationship. Gender also had multiple interaction effects with social support and perceived pandemic risk on anxiety. Overall, the study confirms that COVID-19 quarantine and perceived risk increase stress and anxiety in college students, with social support playing a buffering role, albeit with variations based on gender.